STRATEGI BERTAHAN HIDUP PEREMPUAN DI SEKTOR INFORMAL PASCA GEMPA 2009 (Studi Kasus Perempuan Penjual Sayur di Pasar Raya Padang) (Universitas PGRI Sumatera Barat, 2011)
This research tell about women trader in informal sector especially vendors incentral market of Padang. There is an increasing appreciation in the societytowards women as the women empowerment movement comes into various field.This time women role have contributed in fulfilling the families economic somuch the felt. This research want to explain earthquake consequence and vendorswomen livehood strategies also gender relation of their families.Result of research : 1) The vendors women in the central market of Padang havecontributed in fulfilling the family's economic necessities when their husbands hasfaced difficulties in providing basic necessities of their families. 2) The September2009 earthquake in West Sumatera has caused less income for vendors in thecentral market of Padang. This condition motivates them to make strategies fortheir survival and continuing their children education's. There are severalstrategies done by the vendors, such as moving to other places all the time,extending the trading time and getting loan from other people. 3) The shift in thejob role has changed the role of women. The wife's salary could be the mainincome for their families while the husband's salary as the secondary income.Women was domain to taked conclusion such as children education's, boughtanother thing for their families etc